Safety and immunogenicity of a live attenuated mumps vaccine: A phase I clinical trial - Liang, Yan (Hum Vaccin Immunother, 2014)
Background: Mumps, a communicable, acute and previously well-controlled disease, has had recent and occasional resurgences in some areas. Methods: A randomized, double-blind, controlled and multistep phase I study of an F-genotype attenuated mumps vaccine produced in human diploid cells was conducted. A total of 300 subjects were enrolled and divided into 4 age groups: 16–60 years, 5–16 years, 2–5 years and 8–24 months. The groups were immunized with one injection per subject. Three different doses of the F-genotype attenuated mumps vaccine, A (3.5 ± 0.25 logCCID(50)), B (4.25 ± 0.25 logCCID(50)) and C (5.0 ± 0.25 logCCID(50)), as well as a placebo control and a positive control of a licensed A-genotype vaccine (S79 strain) were used. The safety and immunogenicity of this vaccine were compared with those of the controls. Results: The safety evaluation suggested that mild adverse reactions were observed in all groups. No serious adverse event (SAE) was reported throughout the trial. The immunogenicity test showed a similar seroconversion rate of the neutralizing and ELISA antibody in the 2- to 5-year-old and 8- to 24-month-old groups compared with the seroconversion rate in the positive control. The GMT of the neutralizing anti-F-genotype virus antibodies in the vaccine groups was slightly higher than that in the positive control group. Conclusions: The F-genotype attenuated mumps vaccine evaluated in this clinical trial was demonstrated to be safe and have effective immunogenicity vs. control.